Python-based software for solving clever PDEs - Basim K. Abbas, Nadia Mahmood Hussien, Yasmin Makki Mohialden, kawakib Mahmood Hussien (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Several recent investigations have identified a technique for approximating solutions to partial differential equations (PDEs). However, there was little room for adaptive frameworks that facilitate the exploration of new concepts. We can compensate by using the PyDEns library in Python. Using the PyDEns module and the open-source Batch Flow framework, you can solve a variety of partial differential equations. There are partial differential equations, such as those that describe heat and waves, and other equations, such as this one. In this article, we explain how to solve differential equations using neural networks using a new method introduced by Python PyDEns. Partial differential equations can be solved with this software tool.